Tribute, Phenotype and Genealogy. Indian and Nation in the Colombian Caribbean during the Nineteenth Century - Paolo Solano, Sergio (Revista Complutense de Historia de América, 2012)
In this paper we study what was an Indian in the Colombian Caribbean region during the nineteenth century. This is a topic of interest for those areas of the geography of this country and the rest of Latin America is not associated with the presence of Indians, to be given or be extinct because its inhabitants are identified with other ethnic characteristics. We argue that during this century, the Republican state played a leading role in defining Indian identity, as he did the colonial state, in dealing with ethnic nature relationship had institutional implications. We show that the Indians took advantage of political conflict between the leading sectors and the Republican rules.
Keywords: Colombian Caribbean; Indigenous; Reservations; Nation; Identity; Tribute; Phenotype; Genealogy; Colombia; XIXth Century.